Analisis Eksistensi Pedagang Berpindah Pada Pasar Nagari di Kecamatan Kamang Baru Kabupaten Sijunjung, di Tinjau dalam Kajian Sosiologi Ekonomi - Sri Rahayu; Ariesta; Irwan (Penerbit STKIP PGRI Bangkalan, 2018)
The main focus of this research is to know the persistence of traders on the marketmove in Kecamatan Kamang Baru Kabupaten Sijunjung, Provinsi Sumatera Barat seenfrom the process of shifting market formation and behavioral patterns of actors in takingeconomic action and see the existence of traders in the market move. The approach used isqualitative approach with data collection method of observation, document and in-depthinterview. The selection of informants was done by purposive sampling and analyzed byMiles & Huberman. The theory used is the theory of Max Weber, on the understanding ofactors acts expressed as social action as far as the action is concerned with the behaviorof other individuals and therefore directed at a particular purpose. The results of thisstudy indicate that the nagari market in Kecamatan Kamang Baru Kabupaten Sijunjunghas been around since the 1940's, called Pasar Pintu Batu, as a nagari market. Currentlythe number of traders nagari market to move that is 8 markets. Market activity isconducted from 07.00-12.00 WIB. The persistence of nagari market traders moves due toseveral things, namely economic or income, morals, culture and trust. From the aboveresults it can be concluded that traders in the market are shifting due to the condition ofcreating a good relationship between the seller and the buyer and the community aroundthe nagari market. Then the actions taken by the merchant and the seller as well as thecommunity have the same goal of gaining profit on the action taken.